2020
DOI: 10.3390/su12041299
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Bike-Sharing Usage around Rail Transit Stations: Evidence from Beijing, China

Abstract: As an emerging mode of transport, bike-sharing is being quickly accepted by Chinese residents due to its convenience and environmental friendliness. As hotspots for bike-sharing, railway-station service areas attract thousands of bikes during peak hours, which can block roads and pedestrian walkways. Of the many works devoted to the connection between bikes and rail, few have addressed the spatial‒temporal pattern of bike-sharing accumulating around station service areas. In this work, we investigate the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Thirdly, to the best of our knowledge, there is little work done on simultaneously exploring the characters of two bike sharing systems (SBBS and FFBS) as transfer modes to rail transit station areas in one city. The existing literature focuses on the integration of rail transit with a single bike sharing system, either SBBS (e.g., Ma et al, 2018;Martin & Shaheen, 2014;Nair et al, 2013;Yang et al, 2016) or FFBS (e.g., Lin et al, 2019;Wang et al, 2020;Zhou et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, to the best of our knowledge, there is little work done on simultaneously exploring the characters of two bike sharing systems (SBBS and FFBS) as transfer modes to rail transit station areas in one city. The existing literature focuses on the integration of rail transit with a single bike sharing system, either SBBS (e.g., Ma et al, 2018;Martin & Shaheen, 2014;Nair et al, 2013;Yang et al, 2016) or FFBS (e.g., Lin et al, 2019;Wang et al, 2020;Zhou et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The integration of bike sharing and rail transit can strengthen the win-win benefit, which provides residents with more flexibility and travel choices (Gu et al, 2019a;Wang et al, 2020). As rail transit feeder modes, two bike sharing systems (i.e., SBBS and FFBS) may exhibit different characteristics of user demand due to their different rebalancing strategies (Ma et al, 2020;Pal & Zhang, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…carry out a spatiotemporal characteristic analysis of the relationship between the bike-sharing usage in railwaystation service areas and its determinants, including the passenger flow in stations, land use, bus lines and roadnetwork characteristics [28]. However, the literature review has not identified any in-depth analyses of city bike user stopovers to identify and delimit attractive public spaces.…”
Section: Literature Reviewmentioning
confidence: 99%
“…eir objectives are to reduce congestion, gas emissions, and noise and to offer a flexible and cheap means of transport while having a beneficial effect on the health of users [6]. ey allow users to make relatively short journeys, of the order of 2.5 km [7] while integrating with other modes of transport in the intermodality context [8]. In addition, these systems provide a flexible mode of transport that improves "first mile/last mile" connections [9]; this distance is considered too long to walk between home and public transport and/or public transport and the workplace [10].…”
Section: Introductionmentioning
confidence: 99%